2013
DOI: 10.1002/ejic.201300636
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Supramolecular Coordination Behaviour of a Bis(bidentate) Tetraphosphane

Abstract: The bis(bidentate) phosphane cis,trans,cis-1,2,3,4-tetrakis-(diphenylphosphanyl)cyclobutane (dppcb) has been used for the synthesis of supramolecular complexes, so-called dyads and triads. Depending on the monometallic precursor compound [Ru(bpy) 2 (dppcb)](PF 6 ) 2 or [Ru(bpy) 2 (cis-dppcbO 2 )]-(PF 6 ) 2 [bpy = 2,2Ј-bipyridine, cis-dppcbO 2 = cis,trans,cis-1,2bis(diphenylphosphanoyl)-3,4-bis(diphenylphosphanyl)cyclobutane], [Ru(bpy) 2 (dppcb)NiBr 2 ](PF 6 ) 2 (1) or ΔΛ/ΛΔ-[{Ru(bpy) 2 (cis-dppcbO 2 )} 2 NiBr]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Only in three palladium complexes was the metal atom positioned at the flap instead of the carbon atom (in the structures where the carbon atoms belonged to the four-membered hydrocarbon ring and the exocyclic H–C–C–H torsion indicated a cis configuration; CSD Refcodes: NIDYIK, QUBGID and QUBGOJ) [24,25]. However, in analogous Pd complexes with the four-membered hydrocarbon ring and the trans configuration at the same torsion, the metallacycle ring had, as usual, a carbon atom at the envelope flap (CSD Refcodes: OFAQET, OFAQIX and OFAQUJ) [26]. This asymmetry observed in the metallacycle structure is probably beneficial for transition-metal-promoted asymmetric transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Only in three palladium complexes was the metal atom positioned at the flap instead of the carbon atom (in the structures where the carbon atoms belonged to the four-membered hydrocarbon ring and the exocyclic H–C–C–H torsion indicated a cis configuration; CSD Refcodes: NIDYIK, QUBGID and QUBGOJ) [24,25]. However, in analogous Pd complexes with the four-membered hydrocarbon ring and the trans configuration at the same torsion, the metallacycle ring had, as usual, a carbon atom at the envelope flap (CSD Refcodes: OFAQET, OFAQIX and OFAQUJ) [26]. This asymmetry observed in the metallacycle structure is probably beneficial for transition-metal-promoted asymmetric transformations.…”
Section: Resultsmentioning
confidence: 99%
“…The resonances of the RuP 2 moiety in 2 occur at 85.8 and 82.2 being also typical. 5,6 Both signals are again doublets of doublets in line with 2 J (P,P) + 3 J (P,P) cis of 27.0 Hz and 3 J (P,P) trans of 11.9 Hz in the former and 3 J (P,P) trans of 13.0 Hz in the latter case. Due to the presence of 195 Pt satellites also the assignments of the resonances in 3 and 4 are unequivocally possible.…”
Section: Synthetic Procedures and Investigation In Solutionmentioning
confidence: 85%
“…4 Phosphine ligands show an enormous stability when combined with soft metals and are often considered "spectator ligands", since their electronic properties do not influence the low lying absorption bands or emission properties of the complexes containing chromophoric units. Specifically tetraphosphines are capable of a versatile supramolecular coordination behaviour 5 and dyads derived thereof lead to active catalysts for photochemical water splitting. 6 Only recently, it has been shown that the photocatalytic activity for hydrogen production originates from a selforganization process in the case of a heteroleptic photosensitizer of the type [Cu(P^P)(N^N)] + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other rctt tetrasubstituted cyclobutane derivatives have a more marked butterfly conformation, which apparently results from steric restrictions imposed by bulky substituents (e.g. Strabler et al, 2013). In the case of the title compound, the cis benzoyl and nitrobenzene groups are oriented Molecular structure of the title cyclobutane, with displacement ellipsoids at the 30% probability level for non-H atoms.…”
Section: Structural Commentarymentioning
confidence: 99%